Pre managed earnings benchmarks and earnings management of Australian firms - Sun, L.; Rath, Subhrendu (University of Wollongong, School of Accounting and Finance, 2012)
This study investigates benchmark beating behaviour and circumstances under which managers inflate earnings to beat earnings benchmarks. We show that two benchmarks, positive earnings and positive earnings change, are associated with earnings manipulation. Using a sample of Australian firms from 2000 to 2006, we find that when the underlying earnings are negative or below prior year’s earnings, firms are more likely to use discretionary accruals to inflate earnings to beat benchmarks.